Preventing crude oil adhesion using fully waterborne coatings. Issue 5 (20th February 2019) - Wu, Xu; Zhang, Yichun; Liu, Minhuan; Xu, Xiubin; Wang, Zhengping; Wyman, Ian; Yang, Hui; Liu, Fanghui; Wang, Jinben; Wu, Jiazhong
Abstract: The petroleum industry has focused on the modification of crude oil composites to decrease their adhesion onto materials and thus facilitate oil extraction, transportation, storage, and processing. However, these methods such as heating, dilution, emulsification, or additives are often accompanied by significant costs and suffer from various limitations. Herein, we present a conceptually different coating strategy that allows many substrates to repel crude oil. The novel coating was achieved via a fully waterborne polymer crosslinkable system consisting of polymer particles, a silicone surfactant, and a melamine formaldehyde resin. Considering the unique anti‐crude‐oil‐adhesion properties, the outstanding physical and chemical stability, as well as the green and industrially‐viable process involved, we anticipate that this coating can provide a promising starting point toward the functionalization of the surfaces of equipment or pipelines that are routinely exposed to crude oils.